শতাব্দী পেরিয়ে - রনো, হায়দার আকবর খান (ঢাকা : তরফদার প্রকাশনী, 2021)
Autobiography of a communist political leader from Bangladesh.
Donated By Akbar Ali Khan
Keywords: Khāna, Hāẏadāra Ākabara, -- 1942-; Communist Party of Bangladesh; Politicians -- Bangladesh -- Biography; Communists -- Bangladesh -- Biography; Bangladesh -- Politics and government -- 1971-